Pengaruh Literasi Digital dan Kepercayaan terhadap Penggunaan Layanan Kependudukan: Studi Perubahan Data akibat Pemekaran: indonesia - Haq, Sumayyah Tsabitul; Paputungan, Irving Vitra; Setiaji, Hari (UII, 2026)
The digital transformation of population administration services has become a strategic effort to enhance the efficiency of public services, especially in regions undergoing administrative expansion. This study aims to examine the influence of digital literacy, trustworthiness, and system quality on user behavior in utilizing the SIPENDUDUK online service in Pekanbaru, Indonesia. A quantitative approach was applied using a survey method involving 400 respondents, determined through Slovin’s formula with a 5% margin of error. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both measurement and structural models. The results reveal that digital literacy and trustworthiness significantly affect users perceived usefulness and ease of use, which in turn influence their intention to use and actual usage behavior. Among these, trustworthiness was found to be the most dominant factor directly affecting the intention to use, while digital literacy enhances user perceptions of system benefits and usability. Although system quality contributes to perceived ease of use and usefulness, it does not directly influence the intention to use. These findings highlight the importance of strengthening public trust and improving digital competence to support the successful adoption of digital government services, particularly in the context of dynamic population data management in newly expanded areas.